Soil microbiome of shiro reveals the symbiotic relationship between Tricholoma bakamatsutake and Quercus mongolica - Guo, Hongbo; Liu, Weiye; Xie, Yuqi; Wang, Zhenyu; Huang, Chentong; Yi, Jingfang; Yang, Zhaoqian; Zhao, Jiachen; Yu, Xiaodan; Sibirina, Lidiya Alekseevna (Frontiers in Microbiology, 2024)
Tricholoma bakamatsutake is a delicious and nutritious ectomycorrhizal fungus. However, its cultivation is hindered owing to limited studies on its symbiotic relationships. The symbiotic relationship between T. bakamatsutake and its host is closely related to the shiro, a complex network composed of mycelium, mycorrhizal roots, and surrounding soil. To explore the symbiotic relationship between T. bakamatsutake and its host, soil samples were collected from T. bakamatsutake shiro (Tb) and corresponding Q. mongolica rhizosphere (CK) in four cities in Liaoning Province, China. The physicochemical properties of all the soil samples were then analyzed, along with the composition and function of the fungal and bacterial communities. The results revealed a significant increase in total potassium, available nitrogen, and sand in Tb soil compared to those in CK soil, while there was a significant decrease in pH, total nitrogen, total phosphorus, available phosphorus, and silt. The fungal community diversity in shiro was diminished, and T. bakamatsutake altered the community structure of its shiro by suppressing other fungi, such as Russula (ectomycorrhizal fungus) and Penicillium (phytopathogenic fungus). The bacterial community diversity in shiro increased, with the aggregation of mycorrhizal-helper bacteria, such as Paenibacillus and Bacillus, and plant growth-promoting bacteria, such as Solirubrobacter and Streptomyces, facilitated by T. bakamatsutake. Microbial functional predictions revealed a significant increase in pathways associated with sugar and fat catabolism within the fungal and bacterial communities of shiro. The relative genetic abundance of carboxylesterase and gibberellin 2-betadioxygenase in the fungal community was significantly increased, which suggested a potential symbiotic relationship between T. bakamatsutake and Q. mongolica. These findings elucidate the Ecological relationship between Tricholoma bakamatsutake and Quercus mongolica microbial community and relevant symbiotic environment to better understand the relationship between T. bakamatsutake and Q. mongolica.